Development, testing and validation of a SARS-CoV-2 multiplex panel for detection of the five major variants of concern on a portable PCR platform - Stanhope, Bryce J.; Peterson, Brittany; Knight, Brittany; Decadiz, Ray Nobles; Pan, Roger; Davis, Phillip; Fraser, Anne; Nuth, Manunya; vanWestrienen, Jesse; Wendlandt, Erik; Goodwin, Bruce; Myers, Christopher; et al. (Frontiers in Public Health, 2022)
Many SARS-CoV-2 variants have emerged during the course of the COVID-19 pandemic. These variants have acquired mutations conferring phenotypes such as increased transmissibility or virulence, or causing diagnostic, therapeutic, or immune escape. Detection of Alpha and the majority of Omicron sublineages by PCR relied on the so-called S gene target failure due to the deletion of six nucleotides coding for amino acids 69–70 in the spike (S) protein. Detection of hallmark mutations in other variants present in samples relied on whole genome sequencing. However, whole genome sequencing as a diagnostic tool is still in its infancy due to geographic inequities in sequencing capabilities, higher cost compared to other molecular assays, longer turnaround time from sample to result, and technical challenges associated with producing complete genome sequences from samples that have low viral load and/or high background. Hence, there is a need for rapid genotyping assays. In order to rapidly generate information on the presence of a variant in a given sample, we have created a panel of four triplex RT-qPCR assays targeting 12 mutations to detect and differentiate all five variants of concern: Alpha, Beta, Gamma, Delta, and Omicron. We also developed an expanded pentaplex assay that can reliably distinguish among the major sublineages (BA.1–BA.5) of Omicron. In silico, analytical and clinical testing of the variant panel indicate that the assays exhibit high sensitivity and specificity. This panel can help fulfill the need for rapid identification of variants in samples, leading to quick decision making with respect to public health measures, as well as treatment options for individuals. Compared to sequencing, these genotyping PCR assays allow much faster turn-around time from sample to results—just a couple hours instead of days or weeks.